Pyrazoleamides in Catalytic Asymmetric Reactions: Recent Advances. Issue 14 (4th March 2021) - Meninno, Sara; Franco, Francesca; Benaglia, Maurizio; Lattanzi, Alessandra
Abstract: Pyrazoleamides are a class of compounds which have received significant attention in the last years in asymmetric catalysis as more reactive and practical surrogates of esters or amides. These readily available reagents have served in a variety of diastereo‐ and enantioselective metal‐ and organocatalytic transformations, spanning from simple carbon‐carbon or carbon‐heteroatom bond formation to cascade and rearrangement reactions, to produce valuable classes of heterocyclic compounds. More recently, pyrazoleamides have proved to be pertinent reagents in asymmetric catalysis merged with photoredox catalysis, and in more challenging stereoselective bond‐forming reactions, occurring directly from a visible‐light activated substrate/catalyst complex without any charge separation. Both strategies enable new activation concepts useful for the production of difficult‐to‐access intermediates and pharmaceuticals. In this review, an overview of the progress achieved in asymmetric catalytic reactions of pyrazoleamides from 2015 up to middle 2020, is illustrated. Abstract :